Medicine, marriage and masculinity in early modern England: John Robartes and the library at Lanhydrock House 1630–85. - Aldred, Sophie E (Historical Research, 2025)
This article explores the everyday medical activities and concerns of one man, Lord Robartes. It draws upon the extensive marginalia surviving in Lord Robartes' library to cast light upon his understanding of medicine, the body and his attempts to treat the various ailments of his family: first in an episode relating to a servant, then in the context of his marriages. In doing so, the article elaborates upon the broader cultural, familial and gendered frameworks that inflected the giving of cures and experience of illness in the seventeenth-century household and the role of 'reading' therein.